Lesbian and Bisexual Women in English Canada audio history collection: Cheryl interview - Duder, Karen (1998)
Item consists of sound recordings of Cheryl discussing her childhood in Newfoundland and elsewhere, family life, childhood crushes on girls, teenage years and work, early same-sex relationships, life in the military, later same-sex relationships, and domestic abuse. Digitized 2009/10 (originally recorded 4 November 1998 and 24 November 1998) 3 sound recordings (mp3): 4 November 1998, 1:02:12, 1:02:32; 24 November 1998, 37:13 The Lesbian and Bisexual Women in English Canada audio history collection consists of audio histories conducted for the 2001 University of Victoria Department of History doctoral dissertation "The Spreading Depths: Lesbian and Bisexual Women in English Canada, 1910-1965," by Karen Duder. The collection consists of 12 interviews (21 recordings in total as some were in multiple parts) conducted by Duder from 1996 to 1998. 12 of the 27 women interviewed by Duder consented to their interviews being housed in the University of Victoria Archives. 10 of the 12 women requested to be identified by pseudonym. Digitized with financial assistance of the Government of Canada through the National Archival Development Program of Library and Archives Canada and the Canadian Council of Archives, Undergraduate Reviewed